Effects of service marketing mix on Umrah customer satisfaction: empirical study on Umrah traveling industry in Malaysia - Othman, Bestoon; Harun, Amran; Sadq, Zana Majed; Rashid, Wirya Najm; Abdullah, Kamal Mohammed; Mohammed, Hazhar Omer; Khalid faeq, Dalia (The Mattingley Publishing Co., Inc., 2020)
The objective of this research was to The purpose of this research was to study the customer perception toward marketing mix (product, price, place, promotion, people, process, physical evidence, marketing communication and after sale service), and customer satisfaction of Umrah traveling industry in Malaysia”. “A quantitative study was adopted for collecting data. The customers who performed Umrah more than once were on the focus of this study. The necessary data were collected from 384 respondents through a structured questionnaire using a convenience sampling technique”. “Customer perception toward all dimensions service marketing mix have a positive impact on customer satisfaction. The present study enables the understanding of consumer behavioural features, especially in term of customer satisfaction in Umrah services, particularly in Malaysia and the overall Umrah industry”. “The service sector plays a pivotal role in a country’s economy specifically in Malaysia and part of this sector services is the Umrah services, becomes it is important for commercial activities and contributes to the quality of life. In short, it implies that the role of Umrah services is regarded as a basic need of life”. “Thus, it is imperative to fulfil the requirements and expectations of customers in multifarious backgrounds. This study is an initial effort in investigating the satisfaction of Umrah customers in Malaysia, including their contributing factor, name service marketing mix.